1975
DOI: 10.1139/v75-074
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Lysine-containing Polypeptides. II. The Interaction of Several Sequential Lysine–Glycine Polypeptides with DNA. A Circular Dichroism Study of DNA Conformation in Annealed Complexes

Abstract: To serve as models of protein–nucleic acid complexes, annealed complexes of several sequential lysine–glycine polypeptides with DNA have been formed. Circular dichroic spectra of the DNA contained in the complexes indicates that several discrete conformations of DNA can exist when complexed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

1975
1975
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
4
0
1
Order By: Relevance
“…The CD spectra of the random (LAG)"-DNA complex, at various r values, are shown in Figure 1. These CD spectra are similar to those spectra observed for other systems: complexes of DNA and block (LysA)"(Leu3')m copolymers (Ong and Fasman, 1976), complexes of DNA and sequential (L-Alat.-Lys-i.-Pro)" (Sponar et al, 1973(Sponar et al, , 1975, complexes between DNA and histone HI (Fasman et al, 1970), complexes of poly(i.-lysine) and DNA (Williams and Kielland, 1975;Mandel and Fasman, 1976), and DNA in the presence of NaCl plus either polyethylene oxide or polyacrylate (Jordan et al, 1972). In addition, these ' DNA like spectra (Jordan et al, 1972) are also observed with complexes of DNA and copolymers of L-lysine and L-alanine (Stokrova et al, 1975) and with copolymers of L-lysine and glycine (Williams and Kielland, 1975).…”
Section: Discussionsupporting
confidence: 81%
“…The CD spectra of the random (LAG)"-DNA complex, at various r values, are shown in Figure 1. These CD spectra are similar to those spectra observed for other systems: complexes of DNA and block (LysA)"(Leu3')m copolymers (Ong and Fasman, 1976), complexes of DNA and sequential (L-Alat.-Lys-i.-Pro)" (Sponar et al, 1973(Sponar et al, , 1975, complexes between DNA and histone HI (Fasman et al, 1970), complexes of poly(i.-lysine) and DNA (Williams and Kielland, 1975;Mandel and Fasman, 1976), and DNA in the presence of NaCl plus either polyethylene oxide or polyacrylate (Jordan et al, 1972). In addition, these ' DNA like spectra (Jordan et al, 1972) are also observed with complexes of DNA and copolymers of L-lysine and L-alanine (Stokrova et al, 1975) and with copolymers of L-lysine and glycine (Williams and Kielland, 1975).…”
Section: Discussionsupporting
confidence: 81%
“…ct-DNA exhibits two characteristics peaks (Figure S4 in SI); one positive band around 280 nm complemented to π-π base stacking and a negative band around 245 nm for hellicity4243. While titrated with EB, DNA generates an induced CD signal near 303 nm (Figure S4) along with decreasing π-π stacking peak and increasing helicity peak, which is a well known feature for the intercalation of dye in DNA4445.…”
Section: Resultsmentioning
confidence: 98%
“…Circular dichroism spectroscopic measurements allow to gather information on the DNA secondary structure ( Satpathi et al, 2015 ), being commonly used to monitor nucleic acids structure perturbations ( Tateishi-Karimata and Sugimoto, 2014 ). The dsDNA from salmon testes, used in this work, presents a β-form conformation, exhibiting two characteristic peaks: one positive band at approximately 275–280 nm associated to π–π base stacking and a negative band around 245 nm corresponding to helicity ( Williams and Kielland, 1975 ; Evdokimov et al, 1976 ).…”
Section: Resultsmentioning
confidence: 99%